A Morpho-Mechanical Study of the Contribution of Human Skin Topography to the Characterization of Dynamic Skin Tension during Senescence - H. Zahouani; R. Vargiolu; J. L. Perrot (Recent Updates in Disease and Health Research Vol. 8, 2024)
The structuring of the dermis with a network of collagen and elastic fibres gives a three-dimensional structure to the skin network with directions perpendicular and parallel to the skin surface. This three-dimensional morphology prints on the surface of the stratum corneum a three-dimensional network of lines which express the mechanical tension of the skin at rest. Skin problems are more common in elderly individuals due to the changes in the structures of the skin. To evaluate the changes in skin morphology, a three-dimensional confocal microscopy was used and characterization of skin imaging of volar forearm microrelief was done. Microscopic observations have shown that skin morphology contains a network of lines whose organisation reflects the multidirectional tensions of elastic and collagen fibres in the superficial dermis. We have accurately characterize the role of the skin line network during chronological aging with the identification of depth scales on the network of lines (z \(\) 60\(μ\)m) and the network of lines covering Langer’s lines (z > 60 microns). During aging has been highlighted lower rows for elastic fibres, the decrease weakened the tension and resulted in enlargement of the plates of the microrelief, which gives us a geometric pertinent indicator to quantify the loss of skin tension and assess the stage of aging. The study of 120 Caucasian women shows that ageing in the volar forearm zone results in changes in the morphology of the line network organisation. The decrease in secondary lines (z \(\) 60 \(μ\)m) is counterbalanced by an increase in the depth of the primary lines (z > 60 \(μ\)m) and an accentuation of the anisotropy index. This phenomenon is known to be accelerated by actinic radiation (extrinsic photoageing) which increases the degradation of the elastic fibres.